2019
DOI: 10.1021/acs.joc.9b02960
|View full text |Cite
|
Sign up to set email alerts
|

Photoredox-Catalyzed Hydrosulfonylation of Arylallenes

Abstract: Arylallenes undergo hydrosulfonylation under photoredox-catalyzed conditions. The reaction gives vinyl sulfones in a regio-and diastereoselective manner, employing sodium sulfinates as the sulfonyl source and eosin Y as the photocatalyst. Indol-1-yl, pyrrol-1-yl, phenyl, and naphtylallenes might be used. Aliphatic allenes are incompatible with the reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 74 publications
0
22
0
2
Order By: Relevance
“…The SET oxidation of sulfinic acids and sulfinates for the generation of sulfonyl radicals has been thoroughly explored over the past decades [172]. These oxidations occur under mildly oxidative conditions, and eosin Y (OD13) stands out as an efficient photocatalyst for these steps [175][176][177]. This strategy is also compatible with transition metal catalysis, as shown by Lei and co-workers with an organophotocatalyzed radical cross-coupling method using the aryl sulfinic acids 45.1 and the styrenes 45.2 to generate the allyl sulfones 45.3 (Scheme 45) [178].…”
Section: Scheme 44mentioning
confidence: 99%
“…The SET oxidation of sulfinic acids and sulfinates for the generation of sulfonyl radicals has been thoroughly explored over the past decades [172]. These oxidations occur under mildly oxidative conditions, and eosin Y (OD13) stands out as an efficient photocatalyst for these steps [175][176][177]. This strategy is also compatible with transition metal catalysis, as shown by Lei and co-workers with an organophotocatalyzed radical cross-coupling method using the aryl sulfinic acids 45.1 and the styrenes 45.2 to generate the allyl sulfones 45.3 (Scheme 45) [178].…”
Section: Scheme 44mentioning
confidence: 99%
“…[27] When arylallenes were used as starting compounds in photo- catalytic sulfonylation with sodium sulfinates, the regio-and diastereoselective formation of vinyl sulfones was observed. [28] A photocatalytic approach was also used to synthesize allyl sulfones 37 from styrenes 35 and aryl, hetaryl, and alkyl sulfinic acids 36. [29] The reaction proceeded in chloroform in the presence of (Bu 4 N) 2eosin Y as the photocatalyst as well as Co(dmgH) 2 pyCl and pyridine.…”
Section: Sulfonylation Of Alkenesmentioning
confidence: 99%
“…Photocatalytic sulfonylation of alkenes with sodium sulfinates in the presence of the iridium‐based photocatalyst in DCM led to the formation of hydrosulfonylation products in 13–99% yields [27] . When arylallenes were used as starting compounds in photocatalytic sulfonylation with sodium sulfinates, the regio‐ and diastereoselective formation of vinyl sulfones was observed [28] …”
Section: Sulfonylation Of Unactivated Multiple Bondsmentioning
confidence: 99%
“…In 2020, Voskressensky group found that arylallenes were suitable substrates for photoredox-catalyzed hydrosulfonylation with sodium sulfinates. [22] Sulfonyl radical which was derived from the quenching reaction of the excited photocatalyst eosin Y* with sodium sulfinates was proposed. While the aliphatic allenes were not suitable for this method (Scheme 14).…”
Section: Sulfonylation/noncyclization With Alkenesmentioning
confidence: 99%